“Kotak Kosong” Bernama Paket Paralel Perizinan: Sebuah Content Analysis Kewenangan Perizinan Oleh Pemerintah Daerah Pasca Undang-Undang Cipta Kerja - Muhammad Najih Vargholy; Mohamad Rifan; Syahrul Sajidin; Liavita Rahmawati (Fakultas Hukum Universitas Mulawarman, 2023)
The psychological condition of forming laws and regulations that lead to investment optimization through various licensing and investment policies is an important aspect in viewing the diorama of licensing developments in Indonesia, one of which was initiated by Law Number 11 of 2020 on Job Creation. Displacement specimen decentralized to semi-centralized licensing is one of the consequences of the policy package in the Job Creation Law. This paper was written using the normative research method with 4 (four) types of approaches: statute, conceptual, comparative, and futurist. The discussion in this paper boils down to licensing rationalization at the regional level which is termed